Association Between LMP-1 and p16 Expression with Prognostic Factor of Nasopharyngeal Carcinoma - Rizki Widya Nur; Vega Karlowee; Awal Prasetyo (Universitas Muhammadiyah Semarang, 2023)
Background: LMP-1 and p16 expression are potential biomarkers for nasopharyngeal prognostic factors. EBV interferes with intracellular signaling processes related to cell cycle regulation and LMP-1, inactivating p16 expression and increasing cell proliferation. LMP-1 has been also reported to remove the promoter of p16 via methylation and inactivation of the p16 gene leads to uncontrolled proliferation of cell tumors.Objective: To analyze the association between LMP-1 and p16 expression with prognostic factors of nasopharyngeal carcinoma.Methods: This is a cross-sectional design analyzed that LMP-1 and p16 expression based on immunostaining of nasopharyngeal carcinoma. The patient clinical data used as prognostic factors are histopathological type, quality of life, TNM, and tumor stage. Statistical analysis used chi-square and spearman correlation.Results: Of the 61 patients, 49 were non-keratinizing carcinoma, undifferentiated type (80,3%). About 54 (88.5%) of the 61 samples are LMP-1 positive, 47 of which were non-keratinizing carcinoma. We figured out the significant association between the p16 expression with lymph node involvement (p=0.026) and staging (p = 0.196) in nasopharyngeal carcinoma. No correlation between LMP and p16 expression (p=0,134) (r=-0,194).Conclusion: p16 overexpression is associated with lymph node involvement and advanced stage in nasopharyngeal carcinoma